Climate change disclosure and the promise of response‐ability and transparency: A synthesizing framework and future research agenda. Issue 1 (30th March 2022) - Shui, Xiaolong; Zhang, Minhao; Smart, Palie
Abstract: This paper systematically reviews the burgeoning but fragmented body of literature on climate change disclosure in the first two decades of the 21st century. Although there is an increasing trend for organizations to engage in climate change disclosure, the level of transparency, which is the key to allowing organizations to be responsible and accountable, varies significantly. We have synthesized current research findings on disclosure practice, antecedents, and outcomes into an integrative framework. In light of this framework, a more theoretically informed construct of carbon transparency is introduced in this review paper. We further highlight some research gaps supplementing with promising theorizing opportunities to encourage future works that can go beyond the extant scope of inquiry. Given the urgency of the current carbon budget, more studies are encouraged to examine the mechanism under which carbon transparency can lead to enhanced carbon performance in addressing climate change at the micro‐organization level.